"My Teacher Showed a Different Future": A Narrative Inquiry on Teacher Role Modeling and Students' Career Imagination - dipuro, rahmat; Edy Purwanto; Saukani Nur Akbar; Dr. Ahsan Hakim, M.Pd.I (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
This study uses a narrative inquiry approach to explore how teacher role modeling shapes students' future imagination and reduces career anxiety in an Islamic boarding school (pesantren). In-depth narrative interviews and biographical timelines were conducted with six senior students (santri) and two senior teachers. The findings indicate that teachers who integrate religious piety with entrepreneurial competence are able to construct a counter-narrative against the stigma that pesantren graduates are limited to low-income religious roles. Participants reported increased self-confidence after hearing their teachers' stories. The teachers' authentic stories function as a source of vicarious experience that expands students' career possibilities. This study proposes a moral-entrepreneurial role modeling model as a new typology of teacher role modeling in Islamic education.